2017
DOI: 10.15386/cjmed-781
|View full text |Cite
|
Sign up to set email alerts
|

Infantile hemangiomas: a 7-year experience of a single-center

Abstract: ObjectivesThe aim of the study was to describe the historical and clinical characteristics of hemangiomas in a series of cases of our clinic.MethodsThis is a retrospective study of 36 patients with infantile hemangiomas consulted in our clinic.ResultsWe had 14 multiple hemangiomas, and 1 kaposiform hemangioendothelioma. Almost two-thirds involved the cephalic extremity, and 76% of the cases were treated. Pregnancy risk factors included prematurity, low-birth weight and respiratory distress syndrome. Propranolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
3
0
3
Order By: Relevance
“…Although some doctors previously did not advocate using propranolol as a treatment of IHs in premature infants, recent studies indicated that oral propranolol is safe for preterm and low-birth-weight infants [9, 33, 34]. It was reported that children who start oral propranolol at less than 1 month of age are more likely to develop asymptomatic bradycardia and hypotension [27].…”
Section: Discussionmentioning
confidence: 99%
“…Although some doctors previously did not advocate using propranolol as a treatment of IHs in premature infants, recent studies indicated that oral propranolol is safe for preterm and low-birth-weight infants [9, 33, 34]. It was reported that children who start oral propranolol at less than 1 month of age are more likely to develop asymptomatic bradycardia and hypotension [27].…”
Section: Discussionmentioning
confidence: 99%
“…Nous avons noté une prédominance féminine au cours des anomalies vasculaires cutanées notamment les HI et les AP, ce qui est classique au cours des HI [2,3,10,18] et des AP [7,9].…”
Section: Discussionunclassified
“…Concernant la localisation des lésions, la plupart des lésions d'HI siégeaient à la région céphalique (50,5 %). Ces résultats concordent avec ceux de Bota et al en 2017 [3] et de Adams et al en 2018 [1]. Pour ce qui concerne les AP, la localisation préférentielle, dans notre étude, était la région céphalique (50 %) surtout la face (31,4 %).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…27 studies [7][8][9] investigated prevalence, mainly in America, Germany, Canada, Israel, Japan, Australia, Netherlands, Denmark, China, Mali, and Brazil. 27 studies 7,12,28,[35][36][37]44,45,47,[50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] reported the distribution of IH lesions, and 14 studies 7,12,35,[50][51][52]55,57,59,61,63,64,68,69 surveyed the occurrence of complications. Specifically, 28 studies 7,9,16,[30][31][32]…”
Section: Study Characteristicsmentioning
confidence: 99%